DESIGN OF STABILIZED INFORMATION AND MEASURING SYSTEM PLATFORM FOR INTELLIGENCE OPERATIONS - TKACHUK, ANDRII; BEZVESILNA, OLENA; BONDARCHUK, VASIL; KRYZHANIVSKA, ILONA (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The article presents the results of the design of a stabilized platform of information and measurement system for reconnaissance operations based on robotic mobile tracked platform. The analysis of existing mobile robots for reconnaissance operations was carried out and it was established that all of them are practically effective only in the conditions of work in the open area. A number of ideas, approaches and working hypotheses for the design of a new information and measurement system for reconnaissance operations based on a robotic mobile tracked platform. It has been established that this system is necessary to warn of possible threats of explosions or gas poisoning, rescue operations, etc. The developed design of the robotic caterpillar platform is described, the classical scheme of caterpillar wheels is shown and its movements are described. Attention is paid to the position of the drive, because depending on the orientation in the space of the drive, depends on the direction of rotation of its output shaft, and accordingly the direction of movement of tracked tracks. The expediency of using caterpillar platforms for reconnaissance operations is substantiated. All possible angles of deviation of the stabilized platform from zero position are described. The principle of operation of the stabilized platform of the information-measuring system for conducting reconnaissance operations is mathematically described. It is established that the stabilization of the platform is realized with the help of only two linear accelerometers and motors controlled by an on-board digital computer. The block diagram of the stabilized platform of the information-measuring system for carrying out reconnaissance operations is developed and the admissible error of its stabilization in vertical position is defined.
Keywords: stabilization; accuracy; intelligence; information-measuring system